THE MARRIAGE Trap - 564550 Probst, Jennifer (New York, : Pocket Books, :, 2012)
To satisfy his late father's wishes, billionaire Michael Conte must find a bride: someone who will fit into his traditional family back home in Italy --and fast, so his engaged sister will be allowed to wed. He proposes to fiery, free-spirited photographer Maggie Ryan, to play the part of his fiancě during her trip to Milan for a photo shoot. But once in Italy, sexual tension sparks the hottest no-strings-attached arrangement on any continent.